Physico-Chemical Characteristics and In Vitro Rumen Degradability of Insect Frass as NPN Source for Mineral Blocks in Goats - Tam-is, Rocelyn J.; Gacutan, Jr., Manuel D.; Come, Warren D.; Cimafranca, Lynette C.; Jimenea, John Raphael R. (Future Science / FSH-PH Publications, 2025)
The study was conducted to determine the potential of superworm (Zophobas morio) larvae (SWL) and black soldier fly (Hermetia illucens) larvae (BSFL) frass at 10% inclusion as non-protein nitrogen (NPN) source in formulating mineral blocks for goats, with emphasis on the physico-chemical properties of the mineral blocks, and to assess the extent of feed degradation in goats supplemented with insect frass-based mineral block through an in vitro degradability trial. A total of 16 post-weaned goats were used to determine the effects of supplementing insect frass-based mineral blocks on the feed degradation in goats. The goats were arranged in a randomized complete block design (RCBD) with four (4) treatments and four (4) blocks with initial body weight (BW) as the blocking factor. Treatment A (control), Treatment B (urea molasses mineral block) (UMMB), Treatment C (superworm larvae frass mineral block) (SWLFMB), and Treatment D (black soldier fly larvae frass mineral block) (BSFLFMB) served as treatments. Based on the results, insect frass-based mineral blocks showed potential as a good nutritional supplement for goats. These mineral blocks offer valuable sources of protein, non-protein nitrogen (NPN), and minerals. Evaluation of hardness and solubility indicated that the SWLFMB showed better hardness and compactness, but demonstrated the highest solubility among formulations. In contrast, the UMMB displayed relatively low hardness and compactness, yet was the least soluble of all the mineral block variants. Moreover, in vitro studies showed no significant difference among treatments. Therefore, insect frass-based mineral blocks are a viable alternative source of minerals and NPN for goats, which can be utilized to optimize ruminant feed resources.